Tinjauan Yuridis Perlindungan Tenaga Kerja Indonesia Di Malaysia - Winsherly Tan (Journal of Judicial Review, 2016)
The purpose of this study is to describe clearly about the rights of Indonesia migrant workers who work in Malaysia. Indonesia is the largest migrant-sending countries in ASEAN and the largest migrant-receiving countries of Indonesia in ASEAN is Malaysia. Indonesia itself as a migrant-sending countries already has regulations that governing the protection of the rights of migrant workers working abroad, namely in the Constitution of 1945 set in general on the rights of migrant workers, and more specifically regulates the protection of the rights of Indonesian migrant workers abroad, namely in Law No. 39 of 2004. Malaysia itself also has regulations that governing the protection of migrant workers, namely the 1955 Employment Act.This research is a normative law by using the method of comparative law. The data used in the form of primary and secondary data. Performed with data mining literature (library research). Once all the data is collected both primary data and secondary data, the data is then processed and analyzed, the qualitative analysis was used to group the data point by the studied aspects. Further conclusions drawn related to this study, then described descriptively.Based on the results of this research, Regulations in Indonesia and Malaysia that governs the protection of the rights of migrant workers who work abroad have not been effective in terms of both rules substance and implementation. Memorandum of Understanding (MoU) governing labor migration between the two countries (Malaysia and Indonesia) in 1998 and signed another one on May 10, 2004. MOU made by the two countries also contains many weaknesses in this MOU are not regulated at all about the migrant workers who work at home and have not been effective in protecting the rights of migrant workers.